Not every patient needs a triglyceride check, but all can get pancreatitis: a systematic review and clinical characterization of isotretinoin‐associated pancreatitis. (1st October 2017) - Opel, D.; Kramer, O.N.; Chevalier, M.; Bigby, M.; Albrecht, J.
Summary: Monitoring of triglycerides for patients on isotretinoin is practised primarily to avoid hypertriglyceridaemia‐associated pancreatitis. The aim of this study was to describe clinically the published cases of hypertriglyceride‐associated pancreatitis. A comprehensive search strategy using MEDLINE, Embase and grey literature was conducted (1960 to January 2016) to identify all case reports of isotretinoin‐associated pancreatitis and all relevant studies of isotretinoin and triglycerides for any indication (≥ 20 patients). Terms related to isotretinoin, triglycerides and pancreatitis were searched with all available synonyms. Any studies that used isotretinoin and mentioned triglycerides or pancreatitis were searched in full text, where available, for cases of pancreatitis. Studies from all countries and published in any language were included, but Korean and Turkish studies could not be analysed. Two authors independently reviewed the publications to determine eligibility, and for data extraction. In total, 125 papers fulfilled the inclusion criteria and were searched for cases of pancreatitis. Eleven papers with 25 cases of pancreatitis associated with isotretinoin were identified; four of these cases were likely due to hypertriglyceridaemia. Three patients had elevated baseline triglycerides, but no monitoring. Pancreatitis occurred 6 and 7 weeks, and 6 months after initiation of therapy. For the fourth patient who was treated for glioblastoma and died, no detailed clinical information was available. Idiosyncratic pancreatitis associated with isotretinoin is the most frequent pancreatitis on isotretinoin, and patients should be warned about it. Hypertriglyceride‐associated pancreatitis is an exceedingly rare adverse event of isotretinoin therapy. Our data cannot give a frequency or risk for either adverse event. Based on the clinical information of the patients available, we conclude that for patients without elevated baseline triglycerides, or risk thereof, monitoring of triglycerides during therapy is of little value.